Implementation of value engineering in optimizing project cost for sustainable energy infrastructure asset development - Latif S.D.; Usman F.; Pirot B.M. (International Information and Engineering Technology Association, 2023)
Cost reduction; Floors; Value engineering; Walls (structural partitions); Building projects; Energy utilities; Malaysia; Project cost; Room size; Sustainable energy; Cost engineering; alternative energy; cost analysis; electrical property; energy planning; engineering; floor; project management; wall; Malaysia